FALSAFAH PENDIDIKAN DAN DI PERINGKAT IJAZAH TINGGI DI MALAYSIA - Mat Diah, Abdul Halim (Journal of Al-Tamaddun, 2007)
Islam stresses on the importance of education because of its usefulness in moulding one?s attitude, behavior, thinking, and life in general. For that reason, this article will discuss the purpose of education in Islam based on the teachings of the Qur?an and Hadith, along with the opinions of the classical and modern or contemporary scholars. Besides that, it will discuss the purpose of Islamic Studies in a University and the Philosophy of Islamic Education in Islamic Studies at the higher degree level.